Analisis Perbandingan Material 7075 O (SS) dan Al-SiC Untuk Komponen Roda Gigi Lurus Menggunakan Metoda Finite Elemen Analysis - Muhammad Rival Tanziri; Dani Mardiyana (Universitas Nusa Putra, 2023)
Gears are one of the most widely used types of transmission because they have the ability to transmit large power from one part of the machine to another. The analysis was carried out using solidworks software with a load of 150 N and the material used was 7075 O (SS) or ANSI38 and Al-SiC. Analysis of selecting simulations using software based on the finite element method (finite element analysis program), Finite element analysis is a mathematical numerical technique to calculate the strength and structural behavior of engineering components by dividing objects into mesh shapes, Simulation analysis is carried out using static features by SolidWorks Premium 2022 software. Simulation with this software is useful for carrying out analyzes to prove the validity of a design. The results of the stress analysis for the 7075 O (SS) and Al-SiC materials are 3 N/mm2, the stress for the two materials is still below the yield strength value. Strain or strain of 0.00004 N/mm2 and 0.00002 N/mm2. and displacement or displacement of 0.00133 mm and 0.000626. The weight of the two materials shows that 7075 O (SS) material is lighter with a difference of 0.31046 N. Strain / strain and displacement of Al-SiC material is better than 7075 O (SS) material with a difference of 0.00002 N/mm2 and 0.000704mm.